1988
DOI: 10.1302/0301-620x.70b5.3192563
|View full text |Cite
|
Sign up to set email alerts
|

The Oxford Knee for unicompartmental osteoarthritis. The first 103 cases

Abstract: The Oxford Knee, a resurfacing prosthesis with a meniscal bearing, can be used for either bicompartmental or unicompartmental arthritis. The first 103 unicompartmental cases are presented at a mean time since operation of 36 months (range 21 to 56 months). In those cases with surviving arthroplasties, pain was relieved in 96%. The full range of pre-operative flexion was maintained and flexion deformity was improved from a mean of 6.7 to 5.4 degrees. Stability and alignment were restored to normal in nearly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
1
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(175 citation statements)
references
References 0 publications
4
160
1
5
Order By: Relevance
“…The clinical relevance of this study is that it supports the indication for medial UKR as proposed by Goodfellow et al which states that there should be FTCL on both the femur and tibia, identified by radiology (AP standing, varus stress or PA fixed flexion) or arthroscopy, in the medial compartment to achieve optimal results, as in the setting of PTCL worse results are seen 10 . Whilst some knees with PTCL do achieve good and excellent outcomes at present we cannot identify which knees these will be.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The clinical relevance of this study is that it supports the indication for medial UKR as proposed by Goodfellow et al which states that there should be FTCL on both the femur and tibia, identified by radiology (AP standing, varus stress or PA fixed flexion) or arthroscopy, in the medial compartment to achieve optimal results, as in the setting of PTCL worse results are seen 10 . Whilst some knees with PTCL do achieve good and excellent outcomes at present we cannot identify which knees these will be.…”
Section: Discussionsupporting
confidence: 75%
“…UKR implanted for spontaneous osteonecrosis of the knee, based on radiological or histological diagnosis, or that did not fulfil other criteria for UKR: i) retained full thickness cartilage in the lateral compartment, ii) functionally normal medial collateral ligament (MCL), iii) functionally normal anterior cruciate ligament (ACL), iv) absence of bone loss with grooving to the lateral facet of the patella were excluded from the analysis 10 This cohort of patients was matched, 2:1, using propensity score matching based on age, gender and preoperative Oxford Knee Score (OKS) to knees with FTCL AMOA identified from a consecutive series of 1000 UKR (818 patients) implanted by the designer surgeons, between June 1998 and March 2009, for recommended indications 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Other early reports also included papers by Marmor (1976) and by Scott and Santore (1981) with series of 124 and 100 knees, respectively. Prerequisites for a UKA such as unicompartmental disease, functioning anterior cruciate ligament, tibiofemoral angles between physiological valgus and 10° varus and no subluxation are largely accepted in retrospective studies (Deschamps et al 1987, Goodfellow et al 1994.…”
Section: 1-20; P = 004) Increased Risk Of Revision Compared To Olmentioning
confidence: 99%
“…proposed by Kozinn and Scott, the indications used for the Oxford UKR lie solely with the 46 pathoanatomy of the disease [3]. The Oxford medial UKR is indicated for the treatment of 47 anteromedial osteoarthritis (AMOA) and spontaneous osteonecrosis of the knee (SONK) [3].…”
Section: Introduction 35mentioning
confidence: 99%